Optical coherence tomography analysis at initial diagnosis in patients with retinitis pigmentosa and associated cystoid macular edema - Suk Hoon Jung; Sang Un Yi; Bo-Een Hwang; Young Gun Park; Young-Hoon Park (PLoS ONE, 2025)
This retrospective study analyzed optical coherence tomography (OCT) findings in 130 eyes of 130 patients with retinitis pigmentosa (RP) at initial diagnosis, including 42 with cystoid macular edema (CME) and 88 without, between September 2016 and March 2024. The CME group exhibited increased central macular thickness (CMT) (257.50 ± 104.98 µm vs. 171.40 ± 73.15 µm, p = 0.000), whereas the non-CME group had greater subfoveal choroidal thickness (SCT) (294.52 ± 122.85 µm vs. 246.98 ± 87.31 µm, p = 0.043), total choroidal area (TCA) (4.64 ± 1.98 mm² vs. 3.82 ± 1.34 mm², p = 0.031), stromal area (SA) (1.85 ± 0.76 mm² vs. 1.53 ± 0.54 mm², p = 0.025), luminal area (LA) (2.79 ± 1.22 mm² vs. 2.30 ± 0.81 mm², p = 0.033), and foveal avascular zone in the superficial capillary plexus (FAZ_SCP) (0.42 ± 0.31 mm² vs. 0.27 ± 0.12 mm², p = 0.022). The CME group had more moderate stage cases (47.62% vs. 26.14%, p = 0.015), while the non-CME group had more advanced cases (39.77% vs. 9.52%, p = 0.000). Visual acuity (logMAR) worsened in advanced stages for both groups (CME: 1.62 ± 0.79, p = 0.003; Non-CME: 1.12 ± 0.80, p = 0.000). In the CME group, FAZ in the deep capillary plexus (FAZ_DCP) enlarged from moderate to advanced stages (0.28 ± 0.12 mm² to 0.64 ± 0.09 mm², p = 0.025), and vessel density in the deep capillary plexus (VD_DCP) decreased from early to moderate stages (31.83 ± 3.94% to 28.75 ± 2.71%, p = 0.036), whereas superficial capillary plexus vessel density (VD_SCP) remained stable across stages (early: 32.82 ± 2.59%, moderate: 31.04 ± 2.37%, advanced: 31.52 ± 1.26%, all p > 0.1). The non-CME group exhibited progressive declines in CMT (early: 226.27 ± 38.60 µm, moderate: 195.04 ± 52.56 µm, advanced: 108.83 ± 59.72 µm, all p < 0.01) and choroidal vascularity index (CVI) (early: 0.61 ± 0.02, moderate: 0.60 ± 0.02, advanced: 0.58 ± 0.04, all p < 0.05). In the CME group, visual acuity (logMAR) was positively correlated with cyst area (p = 0.019, rho = 0.361) and FAZ_DCP (p = 0.002, rho = 0.564). These findings suggest that RP-CME may be associated with choroidal atrophy regardless of disease stage and could have a compensatory mechanism to SCP. Cyst area and FAZ_DCP may serve as indicators of visual acuity in RP-CME.